2016
DOI: 10.1039/c6ob01506a
|View full text |Cite
|
Sign up to set email alerts
|

Biphenyl urea derivatives as selective CYP1B1 inhibitors

Abstract: Highly selective CYP1B1 inhibitors have potential in the treatment of hormone-induced breast and prostate cancers. Mimicry of potent and selective CYP1B1 inhibitors, α-naphthoflavone and stilbenes, revealed that two sets of hydrophobic clusters suitably linked via a polar linker could be implanted into a new scaffold 'biphenyl ureas' to create potentially a new class of CYP1B1 inhibitors. A series of sixteen biphenyl ureas were synthesized and screened for CYP1B1 and CYP1A1 inhibition in Sacchrosomes™, yeast-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Microsomal CYP enzymes, isolated from these same recombinant yeast cells, have successfully been used by us earlier as drug discovery tools for screening synthetic compounds and natural product repositories to identify possible cancer chemopreventive agents. [37][38][39] Selection of CYPs for biotransformation of chrysin. In this work, use of recombinant CYPexpressing whole yeast cells has been explored for their ability to be used as biocatalysts for biotransformation reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Microsomal CYP enzymes, isolated from these same recombinant yeast cells, have successfully been used by us earlier as drug discovery tools for screening synthetic compounds and natural product repositories to identify possible cancer chemopreventive agents. [37][38][39] Selection of CYPs for biotransformation of chrysin. In this work, use of recombinant CYPexpressing whole yeast cells has been explored for their ability to be used as biocatalysts for biotransformation reactions.…”
Section: Resultsmentioning
confidence: 99%
“…17β‐estradiol is metabolized by CYP1‐mediated hydroxylation, which is its first and major step in the metabolic process in human breast tumors (Figure a). Due to the importance of this pathway in prevention and treatment of human breast cancer, the inhibitory effect of CYP1B1 by exogenous compounds, including flavonoids, has received considerable attention in the past few years (Androutsopoulos et al, ; Cui et al, ; Mohd Siddique et al, ; Siddique et al, ; Takemura, Itoh, et al, ). The present study, with combining results from enzymatic, computational, and cellular studies, demonstrated that oroxylin A exhibited a more significant inhibitory effect than baicalein on the carcinogenic 4‐OHE2 formation from 17β‐estradiol mediated by CYP1B1 in MCF‐7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Compounds TKR01-TKR21 were synthesised as described methods in previous literatures (all the 1H NMR Spectra of Compounds TKR01-21 in Supporting Information) [17][18][19][20][21][22] .…”
Section: General Procedures For Synthesismentioning
confidence: 99%